Pre- and Perioperative Optimization of a Geriatric Patient on Antithrombotic Therapy Undergoing Dermatologic Electrosurgery: A Case Report - Laila Kurnia Fitri; Subagio (HM Publisher, 2025)
Background: Electrosurgery is a common and effective technique for removing skin lesions and achieving hemostasis in dermatologic surgery. However, managing patients on antithrombotic therapy, especially geriatric patients with comorbidities, presents a significant challenge. This case report highlights the importance of meticulous pre- and perioperative optimization in such patients to ensure safe and successful outcomes. Case presentation: A 69-year-old male patient with a history of congestive heart failure (CHF), Non-ST elevation myocardial infarction (NSTEMI), type 2 diabetes mellitus, and hypertension presented with a nevus exhibiting cornu cutaneous. The patient had been on long-term aspirin therapy. The case discusses the complexities involved in deciding whether to discontinue aspirin, weighing the risks of bleeding against the potential for thrombotic events. After a three-week delay and consultation with an internist to address elevated coagulation parameters, the electrocauterization excision was performed successfully. Conclusion: This case underscores the critical role of multidisciplinary collaboration and evidence-based decision-making in the perioperative management of geriatric patients on antithrombotic therapy undergoing dermatologic procedures. It emphasizes the need for individualized risk assessment and optimization strategies to balance the competing risks of bleeding and thrombosis.